2009
DOI: 10.1371/journal.pone.0008229
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Knockout Mice Reveals a Synergistic Role of the Vav1 and Rasgrf2 Gene Deficiencies in Lymphomagenesis and Metastasis

Abstract: BackgroundVav1 and RasGRF2 are GDP/GTP exchange factors for Ras superfamily GTPases with roles in the development and/or effector functions of T–lymphocytes.Methodology/Principal FindingsGiven that the phenotype of Vav1 –/–, Rasgrf2 –/– and Vav1 –/–;Rasgrf2 –/– mice has been studied so far in young animals, we decided to explore the long–term consequences of the inactivation of those loci in the immune system. Unexpectedly, our studies revealed that the inactivation of the Vav1 proto–oncogene favors the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
1
19
0
4
Order By: Relevance
“…Compare with our results (Fig. 2), aging leukemic Vav1 −/− mice do not show massive thymic enlargement 16 . It could be that initial leukemic cells are produced in a more mature phenotype in aging mice, which do not localize in the thymus.…”
Section: Discussionsupporting
confidence: 56%
“…Compare with our results (Fig. 2), aging leukemic Vav1 −/− mice do not show massive thymic enlargement 16 . It could be that initial leukemic cells are produced in a more mature phenotype in aging mice, which do not localize in the thymus.…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, reduced rasgrf2 gene or protein expression was observed in mammary carcinoma tissues (30), in non-small cell lung cancers (31), and in benign colorectal adenoma as well as invasive colon carcinomas (32). Restoration of RasGRF2 expression resulted in a 56% reduction of colony formation of the colorectal cancer cell line HCT-116 (32), and deletion of RasGRF2 accelerated development of lymphoblastic lymphoma-like tumors in mice (33), suggesting a tumor-suppressive role for RasGRF2. A recent study showed that ␤Arr1 functions as an E3 ligase adaptor in the nucleus to mediate p53 degradation and accumulation of DNA damage in response to chronic stress (23).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the identification here of additional VAV1 genetic alterations in PTCL, including a novel recurrent in-frame deletion resulting in the loss of amino acids 778-786 in the linker region between the SH2 and C-terminal SH3 domains of VAV1, further supports a pathogenic role for VAV1 signaling in T-cell transformation. However, constitutive genetic loss of Vav1 is associated with the development of aggressive T-cell lymphoblastic lymphomas in aged mice (35,36), probably as a result of deregulated oncogenic pathways activated in response to defective Vav1 signaling (37).…”
Section: Discussionmentioning
confidence: 99%